Determination of conditions of operation of clothes for workers of the gas-transport companies - Galagan, T.; Polka, T.; Kolosnichenko, M. (Theory and practice of design, 2015)
The results of the analysis conditions for garment workers gas-transmission companies, which allowed to determine the mode of work and microclimatic conditions of the environment were describes. The analysis and study of the topography of the effects of hazardous and harmful factors on the sites of existing types of clothing as a basis for the development of their list to determine the technical requirements to design.